MENINGKATKAN SEMANGAT BELAJAR SISWA PADA PAI MELALUI METODE INQUIRY BERBASIS TEKNOLOGI DI SMK NU SUNAN AMPEL PONCOKUSUMO - Vina Lailia Rohmatika; Muhammad Hasyim (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The low enthusiasm for learning students in Islamic Religious Education (PAI) is caused by learning methods that are still monotonous and less interesting for students. The purpose of this study was to determine the application of technology-based inquiry methods can increase students' enthusiasm for learning in Islamic Religious Education (PAI) subjects at SMK NU Sunan Ampel Poncokusumo through the application of technology-based inquiry methods. This method was chosen because it can encourage students to participate actively and be more enthusiastic in the learning process and can make them think critically. With the integration of technology, the learning process becomes more interactive and interesting. This study uses a qualitative approach with a case study type as its research method. Data were collected through observation, interview, and documentation instruments. The results showed that the technology-based inquiry method can increase students' active participation in learning, as well as create a more interactive and interesting learning atmosphere. The integration of technology in Islamic Religious Education learning can make students more independent in exploring material widely, improve critical thinking skills and can reduce boredom in the learning process. However, this study also found several challenges and obstacles in implementing this method, including limited internet access, teacher readiness in implementing the method, and obstacles in time management in the learning process. Thus, this study contributes to the development of more effective and innovative learning strategies in the school environment.